(untitled) - Abers, Ernest S. (Boston, 1977)
Book cover the knowledge which the author found that it is necessary to develop forst the basic concepts of mechanics and the properties of light, magnetism, and electricity
Keywords: Physics,Vật lý,Vật lý thiên văn,Astrophysics; History,Lịch sử,Lịch sử,History